Clinical and epidemiological profile of leprosy in João Pessoa, Paraíba, Brazil, between the years 2018 and 2022. - Adrielly da Silva Santos; Rafael Gomes Firmino; José Artur de Paiva Veloso; Egberto Santos Carmo; Júlia Beatriz Pereira Souza; Francisco Patricio de Andrade Júnior (REVISTA CEREUS, 2024)
Objective: To highlight the epidemiological profile of individuals affected by leprosy in João Pessoa, Paraíba, from 2018 to 2022. Methodology: This is a quantitative and descriptive epidemiological study using secondary data from SINAN (Sistema de Informação de Agravos de Notificação) and DATASUS (Departamento de Informática do Sistema Único de Saúde). Simple and relative frequencies were calculated; the Chi-square test of Independence was applied, with p<0.05 considered statistically significant. Results: During the period from 2018 to 2022, 1,195 cases of leprosy were recorded, with 2019 having the highest number of cases, accounting for 27.2% of the total. The epidemiological profile predominantly consisted of males (57%), aged 50 to 59 years (35.73%), with low educational attainment (35.73%), and parda ethnicity (74.14%). There was no association between age group and sex (p=0.53). Regarding clinical classification, multibacillary leprosy was the most common (73.3%), with the dimorphic form being the most prevalent (43.10%). Conclusion: Epidemiological analysis using supplementary data provided insights into the profile of leprosy cases in João Pessoa, highlighting the need for prevention and treatment strategies targeted at the most affected population. The abstract should be logically ordered and succinct, although informative. It should be written in a single paragraph with complete and affirmative sentences. It is recommended that the abstract be written with 100 to 200 words.